2012
DOI: 10.1126/science.1211600
|View full text |Cite
|
Sign up to set email alerts
|

Langerhans Cells Facilitate Epithelial DNA Damage and Squamous Cell Carcinoma

Abstract: Polyaromatic hydrocarbons (PAHs) are prevalent, potent carcinogens, and 7,12-dimethylbenz[a]anthracene (DMBA) is a model PAH widely used to study tumorigenesis. Mice lacking Langerhans cells (LCs), a signatory epidermal dendritic cell (DC), are protected from cutaneous chemical carcinogenesis, independent of T cell immunity. Investigation of the underlying mechanism revealed that LC-deficient skin was relatively resistant to DMBA-induced DNA damage. LCs efficiently metabolized DMBA to DMBA-trans-3,4-diol, an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
110
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(122 citation statements)
references
References 33 publications
8
110
1
3
Order By: Relevance
“…This finding is in line with previous reports that demonstrate that activin A induces the differentiation of Langerhans cells from circulating and skinresident precursor cells , and that transgenic mice overexpressing follistatin in keratinocytes have a strongly reduced number of Langerhans cells (Stoitzner et al, 2005). As these cells promote skin carcinogenesis that is induced by DMBA and TPA, by metabolizing DMBA into a more mutagenic compound and thereby increasing DNA damage (Modi et al, 2012), their accumulation in the epidermis of activin-overexpressing mice could further contribute to the pro-tumorigenic phenotype.…”
Section: A Functional Role Of Activin In Skin Cancersupporting
confidence: 92%
“…This finding is in line with previous reports that demonstrate that activin A induces the differentiation of Langerhans cells from circulating and skinresident precursor cells , and that transgenic mice overexpressing follistatin in keratinocytes have a strongly reduced number of Langerhans cells (Stoitzner et al, 2005). As these cells promote skin carcinogenesis that is induced by DMBA and TPA, by metabolizing DMBA into a more mutagenic compound and thereby increasing DNA damage (Modi et al, 2012), their accumulation in the epidermis of activin-overexpressing mice could further contribute to the pro-tumorigenic phenotype.…”
Section: A Functional Role Of Activin In Skin Cancersupporting
confidence: 92%
“…When LCs are absent, metabolic activation of chemical carcinogens (e.g., DMBA) that induce tumor initiation was impaired (37). Moreover, although DETC-depleted mice manifest higher susceptibility to DMBA/TPA tumorigenesis by themselves (27), combined depletion of DETCs and LCs retained the robust LCdeficient tumor-resistant phenotype (47).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that although Runx3-expressing DCs were essential, they were not sufficient to furnish Runx3-null full tumor resistance. Modi and colleagues (37) showed that absence of epidermal LCs confers complete resistance to DMBA/TPAinduced tumorigenesis. Therefore, we evaluated the involvement of LCs in Runx3-null tumor resistance by immunostaining of epidermal sheets from na€ ve DC Runx3À/À ear skin and flow cytometry (Fig.…”
Section: Runx3 Ablation Decreases Tpa-induced Epidermal Proliferationmentioning
confidence: 99%
“…It is important to recognise that the presence of foreign compounds in the skin can lead to localised effects e.g. Langerhan cells may increase the likelihood of carcinogenesis due to the metabolisation of dermally absorbed PAH (Modi et al, 2012); similar observations of the genotoxicity of benzo[a]pyrene have also been made for metablolisation by kerotinocytes (e.g. Brinkmann et al 2013).…”
Section: Dermal Absorptionmentioning
confidence: 93%